VD_FINDINFO HC / 2010 / 419 vom 9. Juli 2010 - VD Tribunal cantonal (2010)
SUSPENSION DE LA PROCÉDURE, LITISPENDANCE, EXCEPTIONMOYEN DE DÉFENSE, DROIT INTERNATIONAL PRIVÉ | 124a CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 452 CPC, 456a al. 1 CPC, 9 al. 1 LDIP, 9 LDIP